Edukasi Pijat Laktasi pada Ibu Menyusui dengan Aromaterapi Daun Pandan - Arifarahmi Arifarahmi; Melda Amalia (Jurnal Abdimas Kesehatan (JAK), 2022)
The exclusive breastfeeding coverage rate in Jambi is 50.9% but the reality in society is that there are still many breastfeeding mothers who have problems so that they cannot breastfeed their babies for 6 months and cause failure to provide exclusive breastfeeding. Lactation massage is one of the efforts to increase milk production in postpartum mothers. Exclusive breastfeeding is very useful to increase the baby's immune system to avoid various diseases.The purpose of this community service is to increase the knowledge and skills of breastfeeding mothers about lactation massage using pandan leaf aromatherapy. The form of activity is to provide education to breastfeeding mothers in the form of lectures, discussions and practices. Methods with face-to-face and online using teaching aids as well as hands-on practice. Education and practice is carried out once, with a duration of 90 minutes. Pre-test is done before the activity. The output of this activity is an increase in knowledge about lactation massage and the application of pandan leaf aromatherapy. The results of the pre-test showed that the five nursing mothers had never received information about lactation massage and pandan leaf aromatherapy. After the counseling activity, there was an increase in the knowledge and skills of all mothers about lactation massage. The conclusion is that providing information about lactation massage with pandan leaf aromatherapy is very necessary so that nursing mothers have good knowledge and skills and give mothers a feeling of relaxation so that the breastfeeding process can take place exclusively for 6 months and continue until the child is 2 years old.